Improving sensory representations using episodic memory. Issue 6 (30th December 2019) - Görler, Richard; Wiskott, Laurenz; Cheng, Sen
Abstract: The medial temporal lobe (MTL) is well known to be essential for declarative memory. However, a growing body of research suggests that MTL structures might be involved in perceptual processes as well. Our previous modeling work suggests that sensory representations in cortex influence the accuracy of episodic memory retrieved from the MTL. We adopt that model here to show that, conversely, episodic memory can also influence the quality of sensory representations. We model the effect of episodic memory as (a) repeatedly replaying episodes from memory and (b) recombining episode fragments to form novel sequences that are more informative for learning sensory representations than the original episodes. We demonstrate that the performance in visual discrimination tasks is superior when episodic memory is present and that this difference is due to episodic memory driving the learning of a more optimized sensory representation. We conclude that the MTL can, even if it has only a purely mnemonic function, influence perceptual discrimination indirectly.